Migraines, Marriage, and Mascara: Media Coverage of Michele Bachmann in the 2012 Republican Presidential Campaign. (August 2014) - Bystrom, Dianne; Dimitrova, Daniela V.
Recent studies show that women running for vice president or president of the United States as major political party candidates often are covered differently than their male opponents by the media. This study examines Republican presidential candidate Michele Bachmann's television news coverage compared to her male opponents in the months leading up to the primary stage of the 2012 campaign. Our analysis shows that Bachmann received less coverage, which was more often written in the game than issue frame. She was more likely to be associated with masculine than feminine issues. However, Bachmann received less image and negative coverage than her male opponents.